Testing the Feasibility of a Briefer School-based Preventive Intervention with Aggressive Children: A Hybrid Intervention with Face-to-Face and Internet Components - Lochman, John E. (J Sch Psychol, 2017)
This study describes the results from a feasibility study of an innovative indicated prevention intervention with hybrid face-to-face and web-based components for preadolescent youth. This intervention includes a considerably briefer set of face-to-face sessions from the evidence-based Coping Power program and a carefully integrated internet component with practice and teaching activities and cartoon videos for children and for parents. The Coping Power — Internet Enhanced (CP-IE) program introduces a set of cognitive-behavioral skills in 12 small group sessions for children delivered during the school day and 7 group sessions for parents. Eight elementary schools were randomly assigned to CP-IE or to Control, and six children at each school were identified each year based on 4(th) grade teacher ratings of aggressive behavior. Path analyses of teacher-rated disruptive behavior outcomes for 91 fifth grade children, across two annual cohorts, indicated Control children had significantly greater increases in conduct problem behaviors across the 5(th) grade year than did CP-IE children. This much briefer version of Coping Power provided beneficial preventive effects on children’s behavior in the school setting similar to the effects of the longer version of Coping Power. The website materials appeared to successfully engage children, and parents’ use of the website predicted children’s changes in conduct problems across the year.